Topical anti-inflammatory effect of 25% ethanol extract of areca nut (Areca catechu L.) on the diameter and histopathology of osteoarthritis rat knees - Humaryanto, Humaryanto; Sanik, Fathnur; Fairuz, Fairuz (Pharmaciana, 2025)
Osteoarthritis of the knee often requires pharmacological treatments when non-pharmacological methods are insufficient. Yet, these medications can have serious side effects and be costly. Therefore, exploring alternative therapies and herbal remedies becomes a crucial aspect in the management of osteoarthritis. Areca nut is a plant known to possess numerous pharmacological properties. Areca nut (Areca catechu L.) seed extract with 25% ethanol has lipoxygenase enzyme inhibitory activity, one of the mediators of inflammation in the body. This research aimed to evaluate the in vivo anti-inflammatory effect of the topical application of a 25% ethanol extract of areca nut seeds in male white rats with an induced osteoarthritis model. The research employed an experimental pre-post design. Each treatment group consisted of five animals. The induction used in this study was Monosodium Iodoacetate (MIA) with a concentration of 1 mg/200 grams BW. The animals were divided into five groups: positive control (Natrium Diclofenac® Cream), negative control (Vaseline flavum), Treatment I (2.5% extract concentration), Treatment II (5% extract concentration), and Treatment III (7.5% extract concentration). Statistical analysis was conducted using one-way ANOVA (p<0.05) with Duncan’s post hoc test. The ethanol extract of areca nut seeds displayed an anti-osteoarthritis effect, with the 7.5% concentration providing efficacy nearly equivalent to that of the positive control. This was followed by extract concentrations of 5% and 2.5%.